PARP7 as a new target for activating anti-tumor immunity in cancer - Popova, Katerina; Benedum, Johannes; Engl, Magdalena; Lütgendorf-Caucig, Carola; Fossati, Piero; Widder, Joachim; Podar, Klaus; Slade, Dea (EMBO molecular medicine, 2025)
ADP-ribosyl transferases (ARTs) are a family of enzymes which catalyze the addition of a chain (PARylation) or a single moiety (MARylation) of ADP-ribose to their substrates. PARP7 is a mono-ADP-ribosyl transferase (mono-ART) which has recently gained attention due to its emerging role as a negative regulator of the type I interferon (IFN-I) and nuclear receptor signaling, and due to its aberrant expression in cancer, contributing to disease progression and immune evasion. PARP7-mediated ADP-ribosylation can differentially affect protein stability. On the one hand, PARP7-mediated ADP-ribosylation of the transcription factor FRA1 protects it from proteosomal degradation and thereby supports its function in negatively regulating IRF1 and the expression of apoptosis and immune signaling genes. On the other hand, PARP7-mediated ADP-ribosylation of aryl hydrocarbon receptor (AHR) and estrogen receptor (ER) marks them for proteosomal degradation. PARP7 also ADP-ribosylates the ligand-bound androgen receptor (AR), which is recognized by DTX3L-PARP9 that modulate the AR transcriptional activity. In this review, we discuss PARP7 enzymatic properties, biological functions and known substrates, its role in various cancers, and its targeting by specific inhibitors.
Veröffentlicht: 24. März 2025
Gesehen am 10.06.2025